Preparation process of ulva oligosaccharides by self-immobilized enzyme method - YANG Qing, HONG Zhuan, ZHANG Yiping, XIE Quanling, CHEN Weizhu, FANG Hua, WU Jing, JIANG Xian, ZHANG Longtao, JIN Wenhui (Zhongguo niangzao)
To increase the yield of ulva oligosaccharides, the ulva polysaccharide lyase with ferritin tag (Ulvan-F) plasmid vector was constructed by genetic engineering. The self-immobilized enzyme was prepared by leveraging its unique self-assembly properties, and applied to the enzymatic hydrolysis of ulva polysaccharides. The fermentation conditions were optimized by single-factor experiments and response surface methodology, and the reuse rate, yield and molecular mass of ulva oligosaccharides were measured. The results showed that the optimal enzymatic hydrolysis conditions were enzymatic hydrolysis temperature 25 ℃, pH 9.0, and substrate concentration 2.5%. Under these optimized conditions, the ulva oligosaccharides yield reached 27.76 mg/g, the activity of Ulvan-F was still 43.77% after 10 cycles, and the total yield of ulva oligosaccharides was 165.43 mg/g, which was 40.41% higher than that prepared by traditional free enzyme (117.82 mg/g). The average molecular mass of the hydrolysis products by Ulvan-F was 492.36 Da. The Ulvan-F had several advantages, including easy purification under low-speed centrifugation condition, efficient separation from the product, and recycle, which could be applied in the industrial production of ulva polysaccharides macropreparation.